Mobile phone-based surveillance system implemented in Turkana County, Kenya has improved the delivery of animal health and food safety interventions in the county - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
In partnership with the Department of Veterinary Services (DVS), Turkana County, Kenya, we developed and deployed a mobile phone-based surveillance system for livestock diseases and syndromes. It has been used to collect and analyse livestock disease data and abattoir records. The DVS has budgeted for its costs of implementation and appointed technical personnel to run the system. Towards the end of 2018, the DVS used the maps generated by the system to inform the distribution of veterinary vaccines and drugs.